Short-Wave Solar Radiation in the Earth's Atmosphere Calculation, Observation, Interpretation - Melnikova, Irina N.; Vasilyev, Alexander V.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Based on data from an experiment which ran for ten years, this book summarizes the results of the Atmospheric Physics Department of the St. Petersburg University and the Main Geophysical Observatory. The processed data now forms a rich dataset of spectral values of radiative characteristics under different atmospheric conditions. The analysis of this database clearly shows that the solar radiative absorption in a dusty and cloudy atmosphere is significantly higher than assumed to date. Both graduate students of atmospheric sciences as well as scientists and researchers in the field of meteorology and climatology will find a wealth of new data and information in this monograph.
Solar Radiation in the Atmosphere -- Theoretical Base of Solar Irradiance and Radiance Calculation in the Earth Atmosphere -- Spectral Measurements of Solar Irradiance and Radiance in Clear and Cloudy Atmospheres -- The Problem of Retrieving Atmospheric Parameters from Radiative Observations -- Determination of Parameters of the Atmosphere and the Surface in a Clear Atmosphere -- Analytical Method of Inverse Problem Solution for Cloudy Atmospheres -- Analysis of Radiative Observations in Cloudy Atmosphere -- Conclusion.
Keywords: Earth sciences; Geophysics; Planetology; Atmospheric sciences; Space sciences; Earth Sciences; Atmospheric Sciences; Planetology; Geophysics/Geodesy.; Extraterrestrial Physics, Space Sciences; Electronic books